Indicadores de sustentabildiade : um estudo da evolução do conhecimento na área da Administração Pública - Akim, Érica Kushihara (2017)
In a context of multilateral agreements, such as Agenda 21, which states and governments receive the delegation the responsibility for elaborating strategies and sustainable developments plans, knowledge about sustainability indicators have an important role. The objective of this study is investigated the evolution of issue in scientific research published in Web of Science (WoS) in public administration field between 1990 and 2016. The searched for factors for drawing up the trajectory of research, of Kuhn´s perspective, which considers Science as complex relation between theories, data and paradigms and not the gradual accumulation of knowledge. The method used is characterized by exploratory and descriptive, used a bibliometric and systematic analyses, with the support of graphs and views generated by the VOSViewer 1.6.5 and CiteSpace V. The main issues analyzed by this study from the bibliometric perspective are the evolution of publications, authors, institutions and journals. The systematic review identified the evaluation for methodological approach, the presence of sustainability dimensions, the locus and environment studied and topics. This study suggesting that publication between 1990 and 1999 have a great influence of economic approach. Gradually other fields start to be contributed, such as environmental science, planning and urbanism. Another important finding is the prevalence of theoretical and problem-solving studies. About locus studied, the city occupies an outstanding role, mainly in the period 2010-2016. It concludes that the scientific production is currently growing, but is impossible to argue that is consolidated. This is a multifaceted and interdisciplinary issue is related the profusion of topics and roles, but is impossible conclude about the existence the problem and modular solutions shared, which define the paradigm, in Kuhn´s perspective.